How does health promotion work? Evidence from the dirty business of eliminating open defecation - Gertler, Paul (2015)
We investigate the mechanisms underlying health promotion campaigns designed to eliminate open defecation in at-scale randomized field experiments in four countries: India, Indonesia, Mali, and Tanzania. Health promotion works through a number of mechanisms, including: providing information on the return to better behavior, nudging better behavior that one already knows is in her self-interest, and encouraging households to invest in health products that lower the marginal cost of good behavior. We find that health promotion generally worked through both convincing households to invest in in-home sanitation facilities and nudging increased use of those facilities. We also estimate the causal relationship between village open defecation rates and child height using experimentally induced variation in open defecation for identification. Surprisingly we find a fairly linear relationship between village open defecation rates and the height of children less than 5 years old. Fully eliminating open defecation from a village where everyone defecates in the open would increase child height by 0.44 standard deviations. Hence modest to small reductions in open defecation are unlikely to have a detectable effect on child height and explain why many health promotion interventions designed to reduce open defecation fail to improve child height. Our results suggest that stronger interventions that combine intensive health promotional nudges with subsidies for sanitation construction may be needed to reduce open defecation enough to generate meaningful improvements in child health.